„The death of this notable Polish woman is one of the most painful losses, which we have had to mourn in exile”. On the commemoration of loss of life among Polish women during the Great Emigration (Requiem, 2025)
This article aims to review the commemoration of Polish women whose lives were lost during the Great Emigration. Substantial information about these women can be gleaned from a range of sources, particularly written ones, such as obituaries, lists of deceased emigrants, diaries, eulogies, as well as also tombstones. As the following examples illustrate in greater detail, the deaths of these women often reverberated widely among their contemporary refugee community.